Implementing Question-Answer Relationship (QAR) Strategy in Teaching Reading on Practical English Course - Wiranegara, Dian Arsitades; Purbasari, Prima; Hairi, Sohibul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Reading is one of the four language skills that should be mastered in language learning. It is usually taught in integration with one of the other language skills (listening speaking, and writing) in the new trends of language instruction. Generally, the teaching of reading as a foreign language (EFL reading) in PTKIN aims at enabling students to read and comprehend texts and other materials written in English. The study is conducted to overcome the students’ difficulties in reading comprehension and encourage students to actively participate in the teaching-learning process through Question-Answer Relationship (QAR) strategy. The strategy offers four levels of questions (i.e., Right There, Think and Search, Author and Me, and On My Own) to help students answer each level of questions. This strategy comprises three phases: prereading, during-reading, and post reading activities. It is applicable for teaching reading comprehension since it can help and guide the students in comprehending a text well based on the levels of questions.